Safety and Feasibility of Transradial Approach for Coronary Artery Bypass Graft Intervention (Ibrahim Cardiac Medical Journal, 2020)
Background & Objective: To compare the safety and feasibility of using radial versus femoral access during coronary artery intervention of patients who had previously undergone coronary artery bypass graft (CABG) surgery.Methods: The study was conducted in Ibrahim Cardiac Hospital & Research Institute (ICHRI), Dhaka from January 2013 to December 2015. During the period a total of 380 patients with past CABG surgery underwent diagnostic coronary angiogram (CAG) and percutaneous coronary intervention (PCI) at our institution. We retrospectively evaluated 98 consecutive patients who underwent graft intervention via the transradial (TRA, n=54) or transfemoral approach (TFA, n=44) route. Baseline clinical characteristics, angiographic characteristics and complications between the two study groups were observed.Result: The baseline clinical characteristics between the two study groups were similar. No significant difference was observed in terms of angiographic characteristics between the two groups. Contrast volume in between the groups was pretty similar (p = 0.267). Procedure time (40±20 min vs. 41±7 min, p=0.36) and fluoroscopy time (11.1±6.5 min vs. 12.5±8.7 min, p=0.19) were almost similar in both access for graft intervention. All PCI attempts were successful in both groups. Stent deployment was significantly more common in the TR access group. No significant difference was observed between the groups in terms of target vessel intervention. There was no major adverse cardiac event during hospitalization. However, the vascular access site complications were significantly lower (p=0.003) in the TRA group.Conclusion: The TRA for coronary artery bypass graft intervention is safe and feasible.Ibrahim Card Med J 2019; 9 (1&2): 23-28